A Picture of Special Educational Needs in England–An Overview - Black, Alison (Frontiers in Education, 2019)
In this paper I aim to explore and present various statistics regarding special educational needs in England, to get an overview regarding schooling of pupils with Special Educational Needs (SEN) as it is at the time of writing, as well as historic patterns. I use publically available datasets to present answers to the following questions: What proportion of all children in schools in England have been identified as having special educational needs? How many children attend special schools? What proportion of children attend special schools? How have numbers of special schools changed? What is the balance of gender in i/ pupils identified with SEN, and ii/ in special schools? What are the proportions of children in different school types eligible for and receiving free school meals? The use of publically available national data is used to explore patterns, reporting these data give an overview of the number, profile and characteristics of the population in schools with SEN. They give indications on the progress of inclusion (or lack thereof), and highlight issues of disproportionality. Findings include the number of pupils identified with SEN in England decreases while the population of pupils in all schools rises. There is also a rise in the number of children attending special schools. Disproportionality with regards to gender; socio-economic status and age are also revealed.